Evidence of sustained reductions in the relative risk of acute hepatitis B and C virus infections, and the increasing burden of hepatitis a virus infection in Egypt: comparison of sentinel acute viral hepatitis surveillance results, 2001–17 - Talaat, Maha; Afifi, Salma; Reaves, Erik J.; Abu Elsood, Hanaa; El-Gohary, Amany; Refaey, Samir; Hammad, Radi; Abdel Fadeel, Mostafa; Kandeel, Amr (BMC infectious diseases, 2019)
Egypt ranks fifth for the burden of viral hepatitis worldwide. As part of Egypt's renewed national strategy for the elimination of viral hepatitis, surveillance for acute viral hepatitis (AVH) was re-established during 2014-2017 to describe the current epidemiology and associated risk factors, and changes from surveillance conducted during 2001-2004. Patients with suspected AVH were enrolled, completed a questionnaire, and provided blood for testing for hepatitis viruses A (HAV), B (HBV), C (HCV), D, and E (HEV) infections by enzyme-linked immunosorbent assay. Odds ratios and Chi were used to detect differences between hepatitis types by patient characteristics and exposures. Newcombe-Wilson method was used to compare results between surveillance periods 2001-2004 and 2014-2017. Between 2014 and 2017, among 9321 patients enrolled, 8362 (89.7%) had one or more markers of AVH including 7806 (93.4%) HAV, 252 (3.0%) HCV, 238 (2.8%) HBV, and 31 (0.4%) HEV infection. HAV infection occurred most commonly among children < 16 years age, while HBV infection occurred among ages 16-35 years and HCV infection in ages greater than 45 years. Healthcare-associated exposures were significantly associated with HBV and HCV infections compared to HAV infection including receiving therapeutic injections, surgery, wound suture, or urinary catheter and IV line insertions, while significant lifestyle exposures included exposure to blood outside the healthcare system, IV drug use, or incarceration. Exposures significantly associated with HAV infection were attending nursery or pre-school, contact with person attending nursery or pre-school, having meals outside the home, or contact with HAV case. Compared with AVH surveillance during 2001-2004, there was a significant increase in the proportion of HAV infections from 40.2 to 89.7% (RR = 2.3) with corresponding reductions in the proportions of HBV and HCV infections from 30.0 to 2.8% (RR = 0.1) and 29.8 to 3.0% (RR = 0.1), respectively. Healthcare-associated exposures were significantly association with and remain the greatest risk for HBV and HCV infections in Egypt. Additional studies to evaluate factors associated with the reductions in HBV and HCV infections, and cost effectiveness of routine HAV immunization might help Egypt guide and evaluate control measures.